Diffusion of Innovation in Anti-Corruption Education Textbooks and Integrity-Based School Culture Development - Nanang Heliza (BRIDGE : The Multidisciplinary Research Portal, 2025)
Anti-corruption education plays a critical role in fostering integrity, ethical awareness, and responsible citizenship from an early age. This study examines the diffusion of innovation associated with the development and implementation of a localized anti-corruption education textbook in elementary schools in Pesawaran Regency, Indonesia. Guided by Rogers’ diffusion of innovations theory, the research explores the stages of adoption, stakeholder responses, and the contribution of the textbook to integrity-based school culture formation. A qualitative research design was employed, involving semi-structured interviews and open-ended questionnaires administered to school principals, teachers, students, and parents across elementary education units. Data were analyzed using thematic content analysis to identify patterns related to awareness, persuasion, adoption decisions, classroom implementation, and confirmation. The findings indicate that the anti-corruption textbook was widely accepted and effectively integrated into instructional practices due to its contextual relevance, pedagogical flexibility, and strong institutional support. Teachers reported improved instructional confidence, while students demonstrated increased understanding of honesty, responsibility, and fairness in both academic and daily contexts. Furthermore, the innovation contributed to the development of a school culture grounded in integrity and ethical behavior. The study highlights the importance of localized curriculum innovation, policy alignment, and teacher agency in sustaining values-based education. These findings offer theoretical and practical implications for educational policymakers and practitioners seeking to strengthen early anti-corruption initiatives through curriculum-based innovation.